Modelling temperature distributions and flow conditions of fires in an underground mine drift. Issue 6 (1st November 2020) - Hansen, Rickard
Abstract: An analysis on the modelling of fire gas temperatures and fire gas velocities in a mine drift with longitudinal ventilation is conducted. A computational fluid dynamics (CFD) model and a number of empirical correlations are validated against the results from two full-scale fire experiments in a mine drift. During the analysis it is found that the upper level (ceiling) fire gas temperature at 35 and 50 m from the fire is well fitted when comparing the results from the CFD modelling with the experimental results. The fire gas temperatures at the lower level are found to be over predicted by the CFD model. The ceiling fire gas temperatures directly above the vehicles are over predicted in one case and under predicted in the other case by the CFD model. The empirical models are found to over predict the average fire gas temperature during extensive parts of the fires. The fire gas velocities at the higher section are found to be under predicted and the fire gas velocities at the lower section are over predicted by the CFD model. Future studies should be aimed at developing empirical models for mining applications as well as validating developed CFD models.